Immunohistochemical scoring of CD38 in the tumor microenvironment predicts responsiveness to anti-PD-1/PD-L1 immunotherapy in hepatocellular carcinoma. Issue 2 (26th August 2020) - Ng, Harry Ho Man; Lee, Ren Yuan; Goh, Siting; Tay, Isabel Shu Ying; Lim, Xinru; Lee, Bernett; Chew, Valerie; Li, Huihua; Tan, Benedict; Lim, Sherlly; Lim, Jeffrey Chun Tatt; Au, Bijin; et al.
Abstract : Introduction: Hepatocellular carcinoma (HCC) is the fourth leading cause of cancer-associated mortality globally. Immune-checkpoint blockade (ICB) is one of the systemic therapy options for HCC. However, response rates remain low, necessitating robust predictive biomarkers. In the present study, we examined the expression of CD38, a molecule involved in the immunosuppressive adenosinergic pathway, on immune cells present in the tumor microenvironment. We then investigated the association between CD38 and ICB treatment outcomes in advanced HCC. Methods: Clinically annotated samples from 49 patients with advanced HCC treated with ICB were analyzed for CD38 expression using immunohistochemistry (IHC), multiplex immunohistochemistry/immunofluorescence (mIHC/IF) and multiplex cytokine analysis. Results: IHC and mIHC/IF analyses revealed that higher intratumoral CD38 + cell proportion was strongly associated with improved response to ICB. The overall response rates to ICB was significantly higher among patients with high proportion of total CD38 + cells compared with patients with low proportion (43.5% vs 3.9%, p=0.019). Higher responses seen among patients with a high intratumoral CD38 + cell proportion translated to a longer median progression-free survival (mPFS, 8.21 months vs 1.64 months, p=0.0065) and median overall survival (mOS, 19.06 months vs 9.59 months, p=0.0295). Patients with high CD38 + CD68 + macrophage density had a better mOS of 34.43 months compared with 9.66 months in patients with low CD38 + CD68 + macrophage density. CD38 hi macrophages produce more interferon γ (IFN-γ) and related cytokines, which may explain its predictive value when treated with ICB. Conclusions: A high proportion of CD38 + cells, determined by IHC, predicts response to ICB and is associated with superior mPFS and OS in advanced HCC.